2010
DOI: 10.1007/s00775-010-0694-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that His349 acts as a pH-inducible switch to accelerate receptor-mediated iron release from the C-lobe of human transferrin

Abstract: His349 in human transferrin (hTF) is a residue critical to transferrin receptor (TFR)-stimulated iron release from the C-lobe. To evaluate the importance of His349 on the TFR interaction, it was replaced by alanine, aspartate, lysine, leucine, tryptophan, and tyrosine in a monoferric C-lobe hTF construct (FeChTF). Using a stop-ped-flow spectrofluorimeter, we determined rate processes assigned to iron release and conformational events (in the presence and in the absence of the TFR). Significantly, all mutant/TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 29 publications
(62 reference statements)
2
57
0
Order By: Relevance
“…Previous kinetic studies were carried out in a Fe C hTF background (28). Significantly, iron release from this H349A Fe 2 hTF∕TFR complex is preceded by a conformational change with k ¼ 23.7 AE 4.6 min −1 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous kinetic studies were carried out in a Fe C hTF background (28). Significantly, iron release from this H349A Fe 2 hTF∕TFR complex is preceded by a conformational change with k ¼ 23.7 AE 4.6 min −1 .…”
Section: Resultsmentioning
confidence: 98%
“…His349 in hTF (Fig. 4), identified as a pH-inducible switch responsible for iron release from the C lobe in the presence of the TFR (27,28), forms the N-terminal cap of hTF helix α-1. At pH 7.5, His349 interacts through both hydrogen bonds and van der Waals interactions with at least two residues in the C-terminal portion of the TFR including Asp757 and Asn758.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of histidine residues in TfR1 that have been found to be involved in the conformational changes that drive iron release from Tf due to the protonation during endosomal acidification. Further, the Tf residue nearest the junction, His-349, has previously been shown to be essential for release of iron from the C-lobe 36 . His-318 of TfR1 may similarly be required for the transition from a holo-complex to an apo- one, but the stable end states.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that mutation of Lys534 or Arg632 to an alanine severely retards iron release from that lobe, essentially locking iron in the C-lobe (Halbrooks et al, 2003). It has recently become clear that the triad is less relevant to the mechanism of iron release from the C-lobe in the presence of the TFR (Eckenroth, Steere, Chasteen, Everse, & Mason, 2011; Steere, Byrne, et al, 2010) (see discussion of hTF residue His349 below).…”
Section: Transferrinmentioning
confidence: 99%